Stimulant or Depressant? Resource-Related Income Shocks and Conflict - Kai Gehring; Sarah Langlotz; Stefan Kienberger (Center for Economic Studies and ifo Institute (CESifo), 2019)
We provide evidence about the mechanisms linking resource-related income shocks to conflict. Combining temporal variation in international drug prices with spatial variation in the suitability to produce opium, we show that higher drug prices reduce conflict over the 2002-2014 period in Afghanistan. There are two main mechanisms. First, household living standards and thus the opportunity costs of fighting increase. Second, we hypothesize that the opportunity cost effects dominate contest effects if the degree of group competition over valuable resources is sufficiently small. Regressions using georeferenced data on drug production, ethnic homelands, and Taliban versus pro-government influence support this hypothesis.
Keywords: D74; K40; O53; Q10; 330; resources; resource curse; conflict; drugs; illicit economy; illegality; geography of conflict; Afghanistan; Taliban